2016
DOI: 10.1002/uog.14936
|View full text |Cite
|
Sign up to set email alerts
|

Chorioamniotic membrane separation after fetoscopy in monochorionic twin pregnancy: incidence and impact on perinatal outcome

Abstract: Objective To evaluate the incidence of chorioamniotic membrane separation (CMS) after fetoscopy in monochorionic diamniotic (MCDA) twins and its impact on pregnancy outcome. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
47
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 31 publications
5
47
2
Order By: Relevance
“…In other words, the intervention during earlier gestations often caused CMS, which is consistent with the past report by Ortiz et al [7] . The only independent risk factor of CMS was performing the procedure before 20 weeks in this study.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…In other words, the intervention during earlier gestations often caused CMS, which is consistent with the past report by Ortiz et al [7] . The only independent risk factor of CMS was performing the procedure before 20 weeks in this study.…”
Section: Discussionsupporting
confidence: 81%
“…CMS following FLP occurred in 12.7% of cases in this study, whereas other studies have reported 19.6-20.7% [7][8][9] ( Table 2 ). The factor leading to this lower incidence remains to be accounted for, but we speculate that the differences in GA at surgery (proportion of surgery before 18 weeks was 40% in Ortiz et al [7] compared with 11.9% in the present study), type of surgery (including cord occlusion or not), use of tocolysis, and operation procedure affected the lower incidence.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations